Economic imperialism : And The Issues Of Explaining Foreign Phenomena Through Neoclassical Methodology – Analyzed In The Work Of Gary S. Becker - Aalto, Atte (fi=Turun yliopisto|en=University of Turku|, 2018)
Economic imperialism is the phenomenon of scientific imperialism in the science of economics, in which the economic methodology etc. is applied to subject matters that traditionally have been studied by other sciences. The purpose of this thesis is to study to what extent the neoclassical theories of Gary S. Becker can be described as examples of economic imperialism. This is carried out through a review into the literature researching economic imperialism and into the work of Gary S. Becker, with an addition of a descriptive analysis of the economic imperialism present in the work of Gary S. Becker. The analysis reveals fundamental epistemic differences across the theories of Gary S. Becker, with each representing a differing level of scientific imperialism. Furthermore, a review of the literature regarding normativity of scientific imperialism shows that there is no necessary reason to deny the justification of imperialistic research, because it varies case-by-case. The conclusion of the thesis is that the variance in the theories even in a single methodological framework is high enough, that no imperialistic research can be rejected by simply appealing to definition. Additionally, scientific imperialism can be carried out in a way that does not infringe on the sovereignty of other sciences, and if the traditional values of scientific endeavor is accepted, the correct scientific imperialism, including economic imperialism, should be encouraged.